A reactive flow model for hot-spot ignition of shocked aluminized explosives with small size aluminum grains. (March 2017) - Bai, Fan; Liu, Yan; Huang, Feng-Lei; Hussain, Tariq
To predict the influence of aluminum contents (particle size <20 µm) on the shock initiation and growth of reaction in an aluminized explosive (CL-20/AL/Binder, 85/15/5), a new numerical model is utilized. The model is based on the elastic-visco-plastic double hollow sphere pore collapse model (DZK model). In the new model, the aluminum powder combustion is assumed to partly occur during the hot-spot formation. By combining the new term of the hot-spot ignition and the reaction growth term at low pressure and high pressure in the DZK model, a new expression of reaction rate has been implemented in a hydrodynamic code (LS-DYNA) as a user-defined equation-of-state. For verification, the new model has been used to simulate the shock initiation of the aluminized explosive. The numerical results show that 4% of aluminum in this explosive reacts at the stage of hot-spot formation. The model can describe the shock-to-detonation transition process of aluminized explosive while considering the influence of the aluminum contents.